Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications (2023)
Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol-gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human gingival fibroblasts (HGFs) and human dermal microvascular endothelial cells (HDMECs) on three types of silica-coated zirconia surfaces: flat and micropatterned (with pillars and with parallel grooves). Our results showed that cells had a higher metabolic activity (HGF, HDMEC) and increased gene expression levels of fibroblast-specific protein-1 (FSP-1) and collagen type I (COL I) on surfaces with pillars. Nevertheless, parallel grooved surfaces were able to guide cell growth. Even capillary tube-like networks of HDMEC were oriented according to the surface geometry. Zirconia and silica with different topographies have shown to be blood compatible and silica coating reduced bacteria adhesion. All together, the results indicated that microstructured bioactive coating seems to be an efficient strategy to improve soft tissue integration on zirconia implants, protecting implants from peri-implant inflammation and improving long-term implant stabilization. This new approach of micropatterned silica coating on zirconia substrates can generate promising novel dental implants, with surfaces that provide physical cues to guide cells and enhance their behavior. © 2014 National Institute for Materials Science.